Analisis Variabel Internal Perusahaan Terhadap Nilai Perusahaan pada Perusahaan yang Listed di Bursa Efek Indonesia: Analisis Variabel Internal Perusahaan Terhadap Nilai Perusahaan pada Perusahaan yang Listed di Bursa Efek Indonesia - Isnaeni Rokhayati; Dewi Ratna Sari; Harsuti (FEB UNWIKU PURWOKERTO, 2021)
The firm's value reflects the present value of the expected future income. The financial management function can maximize firm value. The purpose of this study was to determine the significance effect of capital structure, dividend policy and firm size on firm value in the Food and Beverage Sub-Sector Companies in Indonesia Stock Exchange. The population in this study were 26 companies from Food and Beverage Sub-Sector in Indonesia Stock Exchange, using a purposive sampling method obtained 12 companies. Data analysis technique using multiple linear regression panel data with the help of Eviews-10 program. The results showed that capital structure had a significant positive effect on firm value, dividend policy had no effect on firm value and firm size had significant negative effect on firm value. This means that the company should still pay attention to the internal factors of the company that can affect company value such as capital structure and company size. This research is limited to only analyzing the variable leverage, capital structure and company carving. Future research should be able to add the company's external factors that can affect firm value such as inflation, interest rates or taxes, as well as increase the observation time of more than five years.